1999
DOI: 10.1007/s004380050986
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of cytosine methylation in an elite rice hybrid and its parental lines, detected by a methylation-sensitive amplification polymorphism technique

Abstract: DNA methylation is known to play an important role in the regulation of gene expression in eukaryotes. In this study, we assessed the extent and pattern of cytosine methylation in the rice genome, using the technique of methylation-sensitive amplified polymorphism (MSAP), which is a modification of the amplified fragment length polymorphism (AFLP) method that makes use of the differential sensitivity of a pair of isoschizomers to cytosine methylation. The tissues assayed included seedlings and flag leaves of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
360
6
8

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 467 publications
(386 citation statements)
references
References 31 publications
12
360
6
8
Order By: Relevance
“…Therefore, 14.78% (275.25/1842) of the 5′-CCGG sites in the genomes of the 20 rice parental lines were methylated. This proportion is slightly smaller than that reported by Xiong et al [19] (16.3%) and Ashikawa [20] (16.2%). However, these two previous studies only considered two rice accessions and any fragment absent from both accessions would not be counted.…”
Section: Variations Of Dna Methylation Across Parental Rice Linescontrasting
confidence: 70%
“…Therefore, 14.78% (275.25/1842) of the 5′-CCGG sites in the genomes of the 20 rice parental lines were methylated. This proportion is slightly smaller than that reported by Xiong et al [19] (16.3%) and Ashikawa [20] (16.2%). However, these two previous studies only considered two rice accessions and any fragment absent from both accessions would not be counted.…”
Section: Variations Of Dna Methylation Across Parental Rice Linescontrasting
confidence: 70%
“…More than 50% of the investigated CCGG sites were found to be stably methylated. Because the use of restriction enzymes does not allow us to distinguish some forms of methylation, MSAP results tend to yield an underestimation of genomic DNA methylation (Xiong et al, 1999). Indeed, recent wholegenome bisulfite sequencing of the maize genome in unfertilized ears revealed that of all Cs in CG and CHG contexts, 86% and 74%, respectively, are methylated (Gent et al, 2013).…”
Section: Discussion the Methylation State Of The Developing Maize Leafmentioning
confidence: 99%
“…These gradual methylation changes are most likely caused by unequal changes in the methylation state of the different cell types that make up the tissues of the harvested samples (Xiong et al, 1999;Peraza-Echeverria et al, 2001;Cervera et al, 2002). For our objectives, the most interesting loci were the CCGG sites that abruptly changed their methylation from one zone to the next.…”
Section: Maize Maintenance Methyltransferases Are Highly Expressed Inmentioning
confidence: 99%
“…To explore the genomic composition of the synthetics relative to their parents, we used two types of AFLP analysis, i.e., standard (Vos et al 1995) and methylation-sensitive (Reyna-Lopez et al 1997;Xiong et al 1999). Standard AFLP analysis was carried out essentially according to the protocol of the AFLP ™ Plant Mapping kit of PE/Applied Biosystems (Foster City, Calif.), with slight modifications (M. Gitzendanner and the Soltis lab, personal communication).…”
Section: Multi-fluorophore Aflp Analysismentioning
confidence: 99%